CHARACTERISTICS OF DYSBIOTIC DISTURBANCES OF STATE WAYS IN WOMEN WITH HYPERPLASTIC PROCESSES AND POLYPES ENDOMETRY - Lisianа T.O.; Ponomarоva I.G.; Kovalchuk, O.A.; Katsalap, O.M.; Gorban, N.E. (World of Medicine and Biology, 2017)
In this work an estimation of microbiocenosis status and analysis of associative forms of infection of the genital tract in 122 women with hyperplastic processes of endometrium and uterine polyps were performed. The obtained data testify that microbiocenosis of the genital tract in patients with hyperplastic processes of endometrium and polyps is characterized by the formation of bacterial complexes and differs in different frequency of pathological manifestations (anaerobic vaginosis, aerobic vaginitis, and candidiasis).